PENGARUH PELATIHAN BERBASIS RISIKO PADA PENINGKATAN KOMPETENSI APARATUR SIPIL NEGARA - Syafitri, Netti; Permata Sari, Dewi; Sumardin, Sumardin; Maizar, Maizar; Sabri, Sabri (Berajah Journal, 2024)
The research entitled "The Effect of Risk-Based Training on Improving the Competence of State Civil Apparatus" aims to analyze the impact of training focusing on risk management on the development of ASN competencies. In the context of a dynamic public sector, risk-based training provides provisions for civil servants to identify, manage, and mitigate potential risks that may be faced in public services. This study uses a literature study approach with data analysis that highlights the importance of training as a human resource development strategy. The results of the study show that risk-based training not only improves the technical skills of ASN, but also strengthens analytical and responsive decision-making abilities in crisis situations. With training designed based on the identification and simulation of real risks, ASN is better prepared to face challenges, which ultimately has a positive impact on the quality of public services. This training plays an important role in supporting ASN to be more adaptive and professional in carrying out their duties. The study emphasizes that investment in risk-based training is very relevant for the development of competent civil servants, in order to support the achievement of organizational goals and increase public trust in government services.